PENGARUH LOCUS OF CONTROL, ORGANIZATIONAL COMMITMENT, KINERJA AUDIT, TURNOVER INTENTIONS, DAN ETIKA PROFESI TERHADAP PERILAKU DISFUNGSIONAL AUDIT (Studi Empiris pada Kantor Akuntan Publik di Kota Pekanbaru, Medan dan Padang) - Intan Mahalayat; Kamaliah Kamaliah; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Audit dysfunctional behavior is behavior that justifies the occurrence of irregularities in the audit, which resulted in a decrease of audit quality both directly and indirectly. This study aimed to determine the effect of locus of control, organizational commitment, performance auditor, turnover intentions and proffesional ethics on dysfunctional audit behavior in public accounting firm in Pekanbaru, Medan and Padang. The population of this study was the auditors in public accounting firm in Pekanbaru, Medan dan Padang with a number of respondents as many as 58 respondents . The samples were determined by using purposive sampling method. Data analysis tools in this study using Structural Equation Modeling-Partial Least Square (PLS-SEM) using smartPLS software Version 3.0. PLS (Partial Least Square). The results showed that the locus of control, organizational commitment, performance auditor, turnover intentions and professional ethics has positive influence to dysfunctional audit behavior.Keywords :locus of control, organizational commitment, performance auditor, turnover intentions, professional ethics, dysfunctional audit behavior